2021
DOI: 10.21101/cejph.a6940
|View full text |Cite
|
Sign up to set email alerts
|

Oral health in a context of public health: prevention-related issue

Abstract: This publication analyses current literary knowledge on selected topics in the fields of oral health and pathology, with a particular emphasis on the potential roles of the oral microbiome and preventative approaches to oral afflictions. An important association with floral dysbiosis has been documented in important oral conditions, sometimes as a predisposing factor and at other times as a result thereof. However, much remains to be elucidated regarding the specific mechanisms at play, as well as their meanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Several studies have demonstrated that health consumers with low health literacy fail to understand the available health information, which would increase health levels and, consequently, their quality of life. Therefore, one of the major health strategies must be focused on the positive interactions between modern healthcare and the population, to establish an integrated health promotion plan focused on disease prevention [18].…”
Section: Defining Oral Health Literacy Strategies In the Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that health consumers with low health literacy fail to understand the available health information, which would increase health levels and, consequently, their quality of life. Therefore, one of the major health strategies must be focused on the positive interactions between modern healthcare and the population, to establish an integrated health promotion plan focused on disease prevention [18].…”
Section: Defining Oral Health Literacy Strategies In the Communitymentioning
confidence: 99%
“…This can be obtained through the development of oral health educational strategies involving all fields among the community, from schools and social support institutions to dental clinics and health centers [18].…”
Section: Defining Oral Health Literacy Strategies In the Communitymentioning
confidence: 99%
“…Over time, new values have been added to health so that today we can look at health from three perspectives: as a right, as a consumer good, and as an investment [ 1 , 2 , 3 ]. The right to health is guaranteed by the WHO (World Health Organization) Constitution [ 4 ], the consumer good is generated by the individual perspective as a material aspect, and the investment in health is important from the point of view of the productive capacity of the labor force.…”
Section: Introductionmentioning
confidence: 99%
“…Disturbance between the balance of enamel demineralization and remineralization leads to dental caries. 5 Dental caries is one of the foremost causes of oral pain and the main reason patients visit dental clinics or hospitals. 2 Moreover, untreated dental caries have a detrimental effect on the quality of life (QoL).…”
Section: Introductionmentioning
confidence: 99%